EDITORIAL: BIOMEDICAL RESEARCH INVOLVING HUMAN SUBJECTS (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Biomedical research involving humans is an emotive issue but paradoxically an essential component in an attempt to improve diagnostic, therapeutic and prophylactic procedures and promote human health. Research data obtained with laboratory animals cannot be extrapolated to predict possible effects of new drugs in humans without being validated in clinical trials. Nevertheless such data is mandatory in weeding out potentially harmful drugs. In some cases these are no suitable laboratory animal models particularly with respect to chronic toxicity such as teratogenicity, carcinogenicity and mutagenicity. Even where suitable animal models are available (for example the chimpanzee) the number of animals used in the experiment is too small to have any meaningful predictive value for a drug which will be used by millions of people.
Keywords: BIOMEDICAL RESEARCH INVOLVING HUMAN SUBJECTS